Zirconia ceramic slurry as well as preparation method and application thereof

By using nano -oxidation powder and color powder, oxidation -oxide ceramic slurry, solve the problem of susceptible damage, complicated preparation process, and narrow color display range of raw blasting, realize high finished product rate, simplify preparation process and expand color The effect of the scope.

CN119371200APending Publication Date: 2025-01-28KUNSHAN IND TECH RES INST INTELLIGENT MFG TECH CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411521706.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-29
Publication Date
2025-01-28

Smart Images

  • Figure CN119371200A_ABST
    Figure CN119371200A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of ceramic slurry, and discloses zirconium oxide ceramic slurry which comprises the following components in percentage by mass: 70-90% of nano zirconium oxide powder, 0.1-3% of colored powder, 5-15% of reactive resin, 1-10% of a plasticizer, 0.1-5% of a photoinitiator, 0.5-5% of an auxiliary agent and the balance of a dispersing agent, the adding amount of the dispersing agent is 1-5% of the sum of the mass of the nano zirconium oxide powder and the mass of the colored powder. According to the method, the colored powder is directly used as the raw material of the zirconia ceramic slurry, so that the zirconia ceramic slurry is the slurry with colors, the green body obtained by additive manufacturing of the zirconia ceramic slurry is the green body with colors, and the finished zirconia material with the target color can be directly obtained through a continuous degreasing and sintering process; the yield is effectively improved, the preparation process is simplified, the treatment time is shortened, and the color range of the zirconium oxide finished product can be widened.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of ceramic slurries, and in particular to a zirconia ceramic slurry and a preparation method and application thereof. Background Art

[0002] Zirconia ceramic photocuring technology is to form a zirconia green body by laser curing a photosensitive resin material mixed with zirconia powder. After degreasing and sintering, the green body is degreased to obtain a ceramic part with performance that meets the requirements. The process mainly includes three steps: material preparation-printing-degreasing and sintering. However, the coloring problem of additively manufactured zirconia ceramics is relatively troublesome. The conventional method is to soak the green body in a dyeing liquid of the corresponding color for a short time after the green body completes the degreasing step, and then further sinter it. This process has the following problems: first, the strength of the green body is very low before degreasing and sintering, and it is very easy to be damaged during the dyeing liquid immersion stage, resulting in a low yield of the sample; second, because the coloring step is located between degreasing and sintering, degreasing and sintering cannot be completed directly, and waiting for the cooling after degreasing and the heating of the sintering section after immersion causes a lot of time and energy waste; third, the green body is colored by soaking in the dyeing liquid, but the green body has a certain limit to the absorption of metal ions in the dyeing liquid, and the color display range of the finished product is narrow.

[0003] Therefore, how to provide a zirconia ceramic slurry with a simple preparation process, high yield and wide color display range is a problem that technical personnel in this field urgently need to solve. Summary of the invention

[0004] In view of this, the present invention provides a zirconia ceramic slurry to solve the problems of easy breakage of green bodies, complex preparation process and narrow color display range of finished products in the existing ceramic slurry coloring process.

[0005] In order to solve the above technical problems, the present invention adopts the following technical solutions:

[0006] In one aspect, the present invention provides a zirconia ceramic slurry, comprising the following components by mass percentage: 70-90% of nano-zirconia powder, 0.1-3% of colored powder, 5-15% of reactive resin, 1-10% of plasticizer, 0.1-5% of photoinitiator, 0.5-5% of auxiliary agent and the balance of dispersant;

[0007] The added amount of the dispersant is 1-5% of the sum of the mass of the nano zirconium oxide powder and the colored powder.

[0008] Preferably, the particle size D of the nano zirconium oxide powder is 50 It is 50-500nm.

[0009] Preferably, the colored powder includes one or more of cerium oxide, erbium oxide, iron oxide, and cobalt oxide.

[0010] Preferably, the reactive resin comprises one or more of hydroxyethyl methacrylate, 1,6-hexanediol diacrylate, tripropylene glycol diacrylate, polyethylene glycol diacrylate, trimethylolpropane triacrylate, trimethylolpropane trimethacrylate, pentaerythritol triacrylate, ethoxylated pentaerythritol triacrylate, pentaerythritol tetraacrylate, ethoxylated pentaerythritol tetraacrylate, tris(3-mercaptopropionic acid)pentaerythritol ester, tetrakis(3-mercaptopropionic acid)pentaerythritol ester, acrylamide and N,N'-methyleneacrylamide.

[0011] Preferably, the plasticizer includes one or more of polyethylene glycol 200, polyethylene glycol 300, polyethylene glycol 400, polyethylene glycol 600, and tetrahydrofuran.

[0012] Preferably, the photoinitiator includes one or more of 2-hydroxy-4'-(2-hydroxyethoxy)-2-methylpropiophenone (PI 2959), 2-hydroxy-2-methyl-1-phenyl-1-propanone (PI 1173), 2,4,6-trimethylbenzoyl-diphenylphosphine oxide (PI184), phenylbis(2,4,6-trimethylbenzoyl)phosphine oxide (PI 819), diphenyl(2,4,6-trimethylbenzoyl)phosphine oxide (PI TPO), benzophenone, benzoin ether compounds, and thioxanthone compounds.

[0013] Preferably, the auxiliary agent includes one or more of Rad2100, Rad2200, Rad2300, Rad2500, Rad2600, Rad2700, diethylene glycol diethyl ether, ethylene glycol butyl ester, dibutyl oxalate, dibutyl phthalate, 3-glycidyloxypropyltrimethoxysilane, 3-(methacryloyloxy)propyltrimethoxysilane, BYK-356, and BYK-361N.

[0014] Preferably, the dispersant includes ammonium polyacrylate, polyvinyl pyrrolidone, sodium alginate, SOLSPERSE24000, SOLSPERSE3000, MALIALIM TM AKM-0531、MALIALIM TM C-20931、MALIALIMSC-1015F、MALIALIM TM One or more of SC-0708A, BYK-108, BYK-109, BYK-111.

[0015] On the other hand, the present invention also provides a method for preparing the above-mentioned zirconia ceramic slurry, comprising the following steps:

[0016] (1) mixing a reactive resin with a dispersant, an auxiliary agent, a plasticizer, and a photoinitiator to obtain a premixed solution;

[0017] (2) dividing the nano zirconium oxide powder into multiple portions, mixing one portion of the nano zirconium oxide powder with the colored powder and the premixed liquid to obtain a mixed liquid;

[0018] (3) Add the remaining zirconium oxide powder to the mixed solution in batches and mix, and obtain zirconium oxide ceramic slurry by degassing and filtering.

[0019] Preferably, the mixing time in steps (1) to (3) is independently 0.5-1 h.

[0020] Furthermore, the present invention further provides a use of the zirconia ceramic slurry described in any one of the above items or the zirconia ceramic slurry prepared by any one of the above preparation methods in additive manufacturing.

[0021] Preferably, a stereolithography printer (SLA printer) or a digital light processing printer (DLP printer) is used for additive manufacturing.

[0022] Preferably, the printing parameters of the stereolithography printer are as follows: laser output power is 0.2-1.5W, scanning rate is 1000-5000mm / s;

[0023] Preferably, the printing parameters of the digital light processing printer are as follows: total power is 1.5-4W, and exposure time is 1-5s.

[0024] The present invention provides a zirconium oxide ceramic slurry, which has the following beneficial effects compared with the prior art:

[0025] The present invention directly uses colored powder as the raw material of zirconia ceramic slurry, so that the zirconia ceramic slurry is a colored slurry, and the green body obtained by additive manufacturing of the zirconia ceramic slurry is a colored green body. The finished zirconia material with the target color can be directly obtained through a continuous degreasing and sintering process, avoiding the step of coloring the green body after degreasing in the conventional process, effectively improving the yield, simplifying the preparation process, and reducing the processing time; and because the colored powder of the present invention is used as the raw material of the zirconia ceramic slurry, the color of the colored powder can be fully utilized and reflected in the finished product, thereby widening the color range of the zirconia finished product; and the present invention makes the final zirconia finished product have good strength by matching the various components and limiting the amount of colored powder added. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on the provided drawings without paying creative work.

[0027] Figure 1 The temperature-time curve of degreasing and sintering of the embodiment of the present invention;

[0028] Figure 2 This is the temperature-time curve of degreasing in Comparative Example 2 of the present invention;

[0029] Figure 3 The temperature-time curve of sintering of Comparative Example 2 of the present invention;

[0030] Figure 4 Schematic diagram of zirconia ceramic slurry of Example 2 of the present invention and Comparative Example 2. DETAILED DESCRIPTION

[0031] The present invention will be described below by specific examples, and it will be appreciated by those skilled in the art that the following specific examples are only for illustrative purposes, and do not limit the scope of the present invention in any way. In addition, in the following examples, unless otherwise specified, the reagents and equipment used are all commercially available. If in the following examples, specific treatment conditions and treatment methods are not clearly described, then conditions and methods known in the art can be used to process.

[0032] In one aspect of the present invention, a zirconia ceramic slurry is provided, which comprises the following components by mass percentage: 70-90% nano zirconia powder, 0.1-3% colored powder, 5-15% reactive resin, 1-10% plasticizer, 0.1-5% photoinitiator, 0.5-5% auxiliary agent and the remainder dispersant.

[0033] It is understandable that the proportion of nano-zirconia powder in the slurry is called solid content. The density of the final product can only be guaranteed when the solid content of nano-zirconia powder is 70-90%. If the amount of nano-zirconia powder added is too little, that is, the solid content is low, the product shrinks too much during the sintering process and the density is difficult to improve. If the amount of nano-zirconia powder added is too much, the viscosity of the slurry is too high, resulting in the inability to print.

[0034] In some embodiments of the present invention, the particle size D50 of the nano zirconium oxide powder is 50-500nm, for example, it can be 50nm, 100nm, 150nm, 200nm, 250nm, 300nm, 350nm, 400nm, 450nm, 500nm, etc. If the particle size of the nano zirconium oxide powder is too small, the viscosity of the slurry will increase, and agglomeration and sedimentation will easily occur. If the particle size is too large, the density of the sintered product will be low and the density requirement will not be met, thereby affecting the permeability, mechanical properties and optical properties of the product.

[0035] In the present invention, the zirconia ceramic slurry includes 0.1-3% of colored powder, specifically 0.1%, 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, etc. In some embodiments of the present invention, the colored powder includes one or more of cerium oxide, erbium oxide, iron oxide, and cobalt oxide, which are used to color the slurry. By adjusting the amount of the added colored powder, the color of the zirconia ceramic slurry can be flexibly adjusted; and in the present invention, since the colored powder is directly used as the raw material of the zirconia ceramic slurry, the color of the powder can be fully utilized to broaden the range of color display.

[0036] In the present invention, the zirconia ceramic slurry includes 5-15% of reactive resin, specifically 5%, 8%, 10%, 12%, 15%, etc. In some embodiments of the present invention, the reactive resin includes one or more of hydroxyethyl methacrylate, 1,6-hexanediol diacrylate, tripropylene glycol diacrylate, polyethylene glycol diacrylate, trimethylolpropane triacrylate, trimethylolpropane trimethacrylate, pentaerythritol triacrylate, ethoxylated pentaerythritol triacrylate, pentaerythritol tetraacrylate, ethoxylated pentaerythritol tetraacrylate, tris(3-mercaptopropionic acid) pentaerythritol ester, tetrakis(3-mercaptopropionic acid) pentaerythritol ester, acrylamide and N,N'-methylene acrylamide, for the photocuring process.

[0037] In the present invention, the zirconia ceramic slurry includes 1-10% plasticizer, specifically 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, etc. In some embodiments of the present invention, the plasticizer includes one or more of polyethylene glycol 200, polyethylene glycol 300, polyethylene glycol 400, polyethylene glycol 600, and tetrahydrofuran, which is used to improve the toughness of the green body, and the hardness of the green body can be adjusted by adjusting the ratio between the reactive resin and the plasticizer.

[0038] In the present invention, the zirconia ceramic slurry includes 0.1-5% of a photoinitiator, specifically 0.1%, 1%, 2%, 3%, 4%, 5%, etc. In some embodiments of the present invention, the photoinitiator includes one or more of 2-hydroxy-4'-(2-hydroxyethoxy)-2-methylpropiophenone (PI 2959), 2-hydroxy-2-methyl-1-phenyl-1-propanone (PI 1173), 2,4,6-trimethylbenzoyl-diphenylphosphine oxide (PI 184), phenylbis(2,4,6-trimethylbenzoyl)phosphine oxide (PI 819), diphenyl(2,4,6-trimethylbenzoyl)phosphine oxide (PI TPO), benzophenone, benzoin ether compounds, and thioxanthone compounds, which are used to initiate the photocuring process.

[0039] In the present invention, the zirconia ceramic slurry includes 0.5-5% of an additive, specifically 0.5%, 1%, 2%, 3%, 4%, 5%, etc. In some embodiments of the present invention, the additive includes one or more of Rad2100, Rad2200, Rad2300, Rad2500, Rad2600, Rad2700, diethylene glycol diethyl ether, ethylene glycol butyl ester, dibutyl oxalate, dibutyl phthalate, 3-glycidyloxypropyltrimethoxysilane, 3-(methacryloyloxy)propyltrimethoxysilane, BYK-356, and BYK-361N, which are used for defoaming and fluidization to improve the quality of the slurry.

[0040] In the present invention, the zirconia ceramic slurry includes a residual dispersant, and the amount of the dispersant added is 1-5% of the sum of the mass of the nano-zirconia powder and the colored powder, for example, 1%, 2%, 3%, 4%, 5%, etc. If the amount of the dispersant added is too low, the dispersion effect is not good, and if the amount of the dispersant added is higher than 5%, the dispersion degree will not be higher, and it will also lead to waste of raw materials. The dispersant includes ammonium polyacrylate, polyvinyl pyrrolidone, sodium alginate, SOLSPERSE24000, SOLSPERSE3000, MALIALIM TM AKM-0531、MALIALIM TM C-20931、MALIALIMSC-1015F、MALIALIM TM One or more of SC-0708A, BYK-108, BYK-109, BYK-111 are used to disperse powders and improve the uniformity of mixing between raw materials.

[0041] On the other hand, the present invention also provides a method for preparing the above-mentioned zirconia ceramic slurry, comprising the following steps:

[0042] (1) The reactive resin is mixed with a dispersant, an auxiliary agent, a plasticizer, and a photoinitiator to obtain a premixed solution.

[0043] In the present invention, the mixing is conventional mixing under room temperature conditions, for example, the mixing can be carried out under stirring and dispersion at a rotation speed of 800 rpm for 0.5 h. There is no special limitation on this and it can be adjusted according to actual conditions.

[0044] (2) Divide the nano zirconium oxide powder into multiple portions, and mix one portion of the nano zirconium oxide powder with the colored powder and the premixed liquid to obtain a mixed liquid.

[0045] In the present invention, the reactive resin, dispersant, auxiliary agent, plasticizer and photoinitiator are all in liquid state, and the nano zirconium oxide powder and colored powder are in solid state, that is, the amount of solid state substance is much greater than the amount of liquid state substance. Adding the nano zirconium oxide powder in multiple times helps the dissolution process, makes the dispersion process faster and more uniform, and avoids agglomeration.

[0046] In addition, the mixing is carried out at room temperature, and the mixed solution is obtained by high-speed dispersion and stirring of the nano zirconium oxide powder, the colored powder and the premixed solution. For example, the mixture can be dispersed and stirred at a speed of 1000 rpm for 0.5 h. There is no special limitation on this and it can be adjusted according to actual conditions.

[0047] (3) Add the remaining zirconium oxide powder to the mixed solution in batches and mix, and obtain zirconium oxide ceramic slurry by degassing and filtering.

[0048] In the present invention, the remaining zirconium oxide powder can be added to the mixed solution in two, three or more times, which can be adjusted according to the actual situation. The mixing is carried out at room temperature, the mixing time is 0.5h, and the degassing is conventional vacuum degassing, which is not particularly limited.

[0049] On the other hand, the present invention also provides an application of the zirconia ceramic slurry described in any one of the above items or the zirconia ceramic slurry prepared by any one of the preparation methods described in the above items in additive manufacturing, specifically, using a stereolithography printer or a digital light processing printer for additive manufacturing.

[0050] In some embodiments of the present invention, the printing parameters of the stereolithography printer are as follows: the laser output power is 0.2-1.5W, and the scanning rate is 1000-5000mm / s. The laser output power can be, for example, 0.2W, 0.5W, 0.8W, 1.0W, 1.2W, 1.5W, etc., and the scanning rate can be, for example, 1000mm / s, 2000mm / s, 3000mm / s, 4000mm / s, 5000mm / s, etc.

[0051] In some embodiments of the present invention, the printing parameters of the digital light processing printer are as follows: the total power is 1.5-4W, and the exposure time is 1-5s, for example, wherein the total power can be, for example, 1.5W, 2W, 3W, 4W, etc., and the exposure time can be, for example, 1s, 2s, 3s, 4s, 5s, etc.

[0052] By limiting the printing parameters, zirconia ceramic materials with excellent mechanical properties can be obtained.

[0053] In the present invention, a green body is obtained by additive manufacturing using a stereolithography printer or a digital light processing printer, and then the green body is subjected to a debinding and sintering process. The debinding and sintering curve is as follows: Figure 1 As shown, after sintering, a colored zirconium oxide product is obtained.

[0054] Example 1

[0055] This embodiment provides a zirconium oxide ceramic slurry, which is composed of the following raw materials: 105g trimethylolpropane triacrylate, 10g tris(3-mercaptopropionic acid) pentaerythritol ester, 30g polyethylene glycol 200 (plasticizer), 20g MALIALIM TM AKM-0708A (dispersant), 10g benzophenone (photoinitiator), 10g Rad2300 (auxiliary agent), 800g zirconium oxide ceramic powder, 15g erbium oxide, wherein the particle size of the zirconium oxide ceramic powder is D 50 It is 0.4μm.

[0056] The preparation method of the zirconia ceramic in this embodiment is as follows:

[0057] (1) Trimethylolpropane triacrylate, pentaerythritol tris(3-mercaptopropionic acid), polyethylene glycol 200, MALIALIM TM AKM-0708A, benzophenone and Rad2300 were mixed and dispersed under stirring at 800 rpm for 0.5 h to obtain a premixed solution;

[0058] (2) pouring the premixed liquid prepared in step (1) into the material cylinder of a dispersing and stirring mixer, adding 3 / 8 of zirconium oxide ceramic powder and erbium oxide, and dispersing and stirring at high speed for 0.5 h to obtain a mixed liquid;

[0059] (3) adding the remaining zirconia ceramic powder into the mixed solution of step (2) in two portions, stirring and dispersing for 0.5 h respectively, degassing by vacuum, and filtering to obtain a pink zirconia ceramic slurry;

[0060] (4) Using a DLP printer to print and shape the zirconia ceramic slurry of step (3) to obtain a green body, degreasing the green body and then sintering it to obtain a pink zirconia ceramic, wherein the laser power of the DLP printer is 3 W and the exposure time is 2 s.

[0061] Embodiment 2-6

[0062] Examples 2-6 are basically the same as Example 1, the only difference being that the raw material composition of the zirconia ceramic slurry is different, and the 3D printing parameters in step (4) are different, see Table 1 for details.

[0063] Table 1

[0064]

[0065]

[0066] Examples 2-6 respectively obtained light pink, yellow, dark yellow, blue and dark pink zirconia ceramic slurries, and the zirconia ceramic finished products obtained after 3D printing and degreasing and sintering were consistent in color with the zirconia ceramic slurries.

[0067] Comparative Example 1

[0068] Comparative Example 1 is basically the same as Example 1, except that the raw material composition of the zirconia ceramic slurry is different. For specific raw material composition of the zirconia ceramic slurry in this comparative example, please refer to Table 2.

[0069] Comparative Example 2

[0070] Comparative Example 2 is basically the same as Example 2, except that the raw material composition of the zirconia ceramic slurry is different and the preparation method of the zirconia ceramic is different. The raw material composition of the zirconia ceramic slurry in this comparative example is specifically shown in Table 2, and the preparation method of the zirconia ceramic is as follows:

[0071] (1) Mix the reactive resin, dispersant, plasticizer, photoinitiator and additive, and stir and disperse at a speed of 800 rpm for 0.5 h to obtain a premixed solution;

[0072] (2) pouring the premixed liquid prepared in step (1) into the material cylinder of a dispersing and stirring mixer, adding 3 / 8 of zirconia ceramic powder, and dispersing and stirring at high speed for 0.5 h to obtain a mixed liquid;

[0073] (3) The remaining zirconia ceramic powder is added to the mixed solution of step (2) in two portions, and stirred and dispersed for 0.5 h respectively. After vacuum degassing and filtration, a white zirconia ceramic slurry is obtained, such as Figure 4 The photo in the middle and lower part shows the white zirconia ceramic slurry of Comparative Example 2, and the photo in the upper part shows the light pink zirconia ceramic slurry of Example 2;

[0074] (4) The zirconium oxide ceramic slurry of step (3) is prepared as follows: Figure 2 After degreasing the curve shown in the figure, take two samples, soak one sample in a standard staining solution containing 10% erbium oxide for 20 seconds, and soak the other sample in a standard staining solution containing 10% erbium oxide for 1 minute (the color will not change after the soaking time exceeds 1 minute), and then take them out and follow the following steps: Figure 3 The curve shown in the figure was sintered to obtain light pink zirconia ceramics and pink zirconia ceramics respectively.

[0075] Comparative Example 3

[0076] Comparative Example 3 is basically the same as Example 3, except that the raw material composition of the zirconia ceramic slurry is different. The raw material composition of the zirconia ceramic slurry in this comparative example is specifically shown in Table 2.

[0077] Comparative Example 4

[0078] Comparative Example 4 is basically the same as Example 4, except that the raw material composition of the zirconia ceramic slurry is different. The raw material composition of the zirconia ceramic slurry in this comparative example is specifically shown in Table 2.

[0079] Comparative Example 5

[0080] Comparative Example 5 is basically the same as Comparative Example 1, and the only difference is: the printing parameters are different. The printing parameters of this comparative example are as follows: SLA: laser power 6W, scanning speed 4200mm / s.

[0081] Comparative Example 6

[0082] Comparative Example 6 is basically the same as Comparative Example 1, and the only difference is: different printing parameters. The printing parameters of this comparative example are as follows: DLP: laser power 2W, exposure time 7S.

[0083] Table 2

[0084]

[0085] The bending strength of the zirconia ceramics prepared in Examples 1-6 and Comparative Examples 1-6 was measured, and the colors of the zirconia finished products prepared in Examples 1-6 and Comparative Examples 1-6 were statistically analyzed, and the results are shown in Table 3. The three-point bending strength was measured according to GB9341-Bending Properties.

[0086] Table 3

[0087] Three-point bending strength (MPa) color Example 1 973 pink Example 2 961 Light pink Example 3 1028 yellow Example 4 927 Dark yellow Example 5 1006 blue Example 6 953 Dark Pink Comparative Example 1 992 White Comparative Example 2 979 Light pink (20s), pink (1min) Comparative Example 3 Unable to form none Comparative Example 4 985 Light Blue Comparative Example 5 Unable to form normally with a lot of overflow / Comparative Example 6 Unable to form normally with a lot of overflow /

[0088] By comparing Example 1 with Comparative Example 1, it can be concluded that Example 1 of the present invention can make the ceramic green body directly colored after sintering, avoiding the phenomenon that the traditional method is easily damaged during the coloring and immersion stage after degreasing, and the strength of the zirconia ceramic prepared by the present invention is basically the same as that of the zirconia ceramic prepared by the traditional method.

[0089] By comparing Example 2 with Comparative Example 2, it can be concluded that the color difference between directly adding colored powders to the ceramic slurry and soaking in traditional dyeing liquid is not much, but compared with the color of the samples soaked for a long time in Comparative Example 2, the color of the zirconia ceramics prepared in Example 6 is darker, indicating that zirconia ceramics with a larger color range can be obtained through the present application.

[0090] By comparing Example 3 with Comparative Example 3, it can be concluded that if the amount of colored powder added exceeds the ratio specified in the present invention, the strength of the zirconia ceramic after sintering will be seriously affected, and even the molding will be impossible.

[0091] By comparing Example 4 with Comparative Example 4, it can be concluded that within the scope of the present invention, the color of the zirconia ceramic can be flexibly adjusted by adjusting the amount of colored powder added.

[0092] Compared with comparative example 1, the printing parameters of comparative examples 5 and 6 exceeded the prescribed range, resulting in scattering of the total light flux, an increase in the solidification area, and the green parts were very easily damaged during the printing process.

[0093] In the description of this specification, the description with reference to the terms "one embodiment", "another embodiment", "yet another embodiment", "some embodiments", "some specific embodiments", "some other specific embodiments" and the like means that the specific features, structures, materials or characteristics described in conjunction with the embodiment are included in at least one embodiment of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of different embodiments or examples, unless they are contradictory. In addition, it should be noted that in this specification, the terms "first" and "second" are used for descriptive purposes only and cannot be understood as indicating or implying relative importance or implicitly indicating the number of technical features indicated.

[0094] Although the embodiments of the present invention have been shown and described above, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations of the present invention. A person skilled in the art may change, modify, replace and vary the above embodiments within the scope of the present invention.

Claims

1. A zirconia ceramic slurry, characterized in that: The composition comprises the following components by mass percentage: 70-90% of nano zirconium oxide powder, 0.1-3% of colored powder, 5-15% of reactive resin, 1-10% of plasticizer, 0.1-5% of photoinitiator, 0.5-5% of auxiliary agent and the balance of dispersant; The added amount of the dispersant is 1-5% of the sum of the mass of the nano zirconium oxide powder and the colored powder.

2. The zirconia ceramic slurry according to claim 1, characterized in that: The particle size D of the nano zirconium oxide powder 50 It is 50-500nm.

3. The zirconia ceramic slurry according to claim 1 or 2, characterized in that: The colored powder includes one or more of cerium oxide, erbium oxide, iron oxide, and cobalt oxide.

4. The zirconia ceramic slurry according to claim 1 or 2, characterized in that: The reactive resin includes one or more of hydroxyethyl methacrylate, 1,6-hexanediol diacrylate, tripropylene glycol diacrylate, polyethylene glycol diacrylate, trimethylolpropane triacrylate, trimethylolpropane trimethacrylate, pentaerythritol triacrylate, ethoxylated pentaerythritol triacrylate, pentaerythritol tetraacrylate, ethoxylated pentaerythritol tetraacrylate, tris(3-mercaptopropionic acid)pentaerythritol ester, tetrakis(3-mercaptopropionic acid)pentaerythritol ester, acrylamide and N,N-methylene acrylamide.

5. The zirconia ceramic slurry according to claim 1 or 2, characterized in that: The plasticizer includes one or more of polyethylene glycol 200, polyethylene glycol 300, polyethylene glycol 400, polyethylene glycol 600, and tetrahydrofuran.

6. The zirconia ceramic slurry according to claim 1 or 2, characterized in that: The photoinitiator includes one or more of 2-hydroxy-4'-(2-hydroxyethoxy)-2-methylpropiophenone, 2-hydroxy-2-methyl-1-phenyl-1-propanone, 2,4,6-trimethylbenzoyl-diphenylphosphine oxide, phenylbis(2,4,6-trimethylbenzoyl)phosphine oxide, diphenyl(2,4,6-trimethylbenzoyl)phosphine oxide, benzophenone, benzoin ether compounds, and thioxanthone compounds; The auxiliary agent includes one or more of Rad2100, Rad2200, Rad2300, Rad2500, Rad2600, Rad2700, diethylene glycol diethyl ether, ethylene glycol butyl ester, dibutyl oxalate, dibutyl phthalate, 3-glycidyloxypropyltrimethoxysilane, 3-(methacryloyloxy)propyltrimethoxysilane, BYK-356, and BYK-361N; The dispersant includes ammonium polyacrylate, polyvinyl pyrrolidone, sodium alginate, SOLSPERSE24000, SOLSPERSE3000, MALIALIM TM AKM-0531、MALIALIM TM C-20931、MALIALIMSC-1015F、MALIALIM TM One or more of SC-0708A, BYK-108, BYK-109, BYK-111.

7. A method for preparing the zirconia ceramic slurry according to any one of claims 1 to 6, characterized in that: The following steps are involved: (1) mixing a reactive resin with a dispersant, an auxiliary agent, a plasticizer, and a photoinitiator to obtain a premixed solution; (2) dividing the nano zirconium oxide powder into multiple portions, mixing one portion of the nano zirconium oxide powder with the colored powder and the premixed liquid to obtain a mixed liquid; (3) Add the remaining zirconium oxide powder to the mixed solution in batches and mix, and obtain zirconium oxide ceramic slurry by degassing and filtering.

8. The method for preparing zirconia ceramic slurry according to claim 7, characterized in that: The mixing time in steps (1) to (3) is independently 0.5 to 1 h.

9. Use of the zirconia ceramic slurry according to any one of claims 1 to 6 or the zirconia ceramic slurry prepared by the preparation method according to any one of claims 7 to 8 in additive manufacturing.

10. The use of the zirconia ceramic slurry in additive manufacturing according to claim 9, characterized in that: Additive manufacturing using stereolithography printers or digital light processing printers; The printing parameters of the stereolithography printer are as follows: laser output power is 0.2-1.5 W, scanning rate is 1000-5000 mm / s; The printing parameters of the digital light processing printer are as follows: total power is 1.5-4W, and exposure time is 1-5s.

Citation Information

Patent Citations

  • Ceramic slurry and preparation method of zirconium oxide-based composite ceramic

    CN107673758A

  • Method for preparing photo-curable dyed dental zirconia ceramic slurry for 3D printing molding

    CN110256069A

  • 3D printing colored zirconia ceramic slurry as well as preparation method and application thereof

    CN117285349A

  • Dental zirconia block having strength, translucency, and color gradient, and method for manufacturing same

    WO2016043378A1